Temperature Behaviour of Pulse Repetition Frequency in Passively Mode-Locked InGaAsP/InP Laser Diode—Experimental Results and Simple Model - Tan, Wei Kiong; Wong, Hin-Yong; Kelly, A. E.; Sorel, Marc; Marsh, John H.; Bryce, A. C. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2007)
In this paper, we report on a laser diode design that can be passively mode locked up to heat sink temperature of 75 degrees C. The dependence of mode-locked frequency and the dependence of the tuning range of the mode-locked laser diode, on operating temperature were investigated. A simple model is presented that can be used to identify the major contributing factors toward the positive shift of mode-locked frequency with temperature. The model takes into account the change of refractive indexes with temperature, change of cavity length with temperature, effect of wavelength shift on refractive indexes, and effect of injected carriers on effective index. While lacking absolute accuracy due to the simplicity of the model, the calculated results demonstrate similar trend to the measured values. The model identifies waveguide dispersion and carrier-induced refractive index change as the major contributing factors to the positive shift of mode-locked frequency with temperature.